Effect of glucose on germination performance in two soybean cultivars - Gorni, Pedro Henrique [UNESP]; Polimeno, Denis Wesley (Universidade Estadual Paulista - Campus de Tupa, 2023)
Glucose promotes increases in physiological processes related to plant growth and induces cell division and can also act in seed germination. The present investigation has been carried out on the influence of various concentrations of glucose on the germination performance of soybeans seeds of cv. BMX and 66i68. Seeds of soybeans (Glycine max (L.) Merrill) were treated with three concentrations of the glucose (0.05, 0.10 and 0.20 mmol L-1), and a control with distilled water. Tests of seed germination and vigor were carried out: it was calculated the germination percentage (first and final counting), percentage of normal seedlings; and speed of germination, length of the primary root and the aerial part of seedlings were recorded. The experiment was arranged in a completely randomized design with three treatments and five repetitions depending on the test. Increasing doses of the plant growth regulator influence the germination and can increase the speed of germination. The use of glucose in the treatment of soybean seeds, increases the rate of germination and emergence speed, growth of the root system and medium of seedlings. Soybean cultivar BMX seeds showed an increase in physiological performance with increasing glucose dosage.
Keywords: germination speed index; Glycine max; phytohormone; root protrusion index; vigor